2022
DOI: 10.1186/s12979-022-00304-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of circadian rhythms on the immune response to influenza vaccination in middle-aged and older adults (IMPROVE): a randomised controlled trial

Abstract: Background Vaccination is important in influenza prevention but the immune response wanes with age. The circadian nature of the immune system suggests that adjusting the time of vaccination may provide an opportunity to improve immunogenicity. Our previous cluster trial in Birmingham suggested differences between morning and afternoon vaccination for some strains in the influenza vaccine in older adults. Whether this effect is also seen in a younger age group with less likelihood of compromised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 37 publications
(36 reference statements)
1
29
0
Order By: Relevance
“…[27] Our previous study found that morning vaccination may enhance the immunogenicity to influenza vaccine in adults aged over 65 instead of those aged 50-60. [8] In the present study, we observed higher neutralizing antibody titers in the younger adults after the second dose of inactivated SARS-CoV-2 vaccine but no significant interaction between age and vaccination time for the antibody response. This is consistent with a recent report studying a retrospective cohort of health care workers immunized with mRNA or Adenovirus SARS-CoV-2 vaccine, which showed no significant interactive effect between age and vaccination time.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…[27] Our previous study found that morning vaccination may enhance the immunogenicity to influenza vaccine in adults aged over 65 instead of those aged 50-60. [8] In the present study, we observed higher neutralizing antibody titers in the younger adults after the second dose of inactivated SARS-CoV-2 vaccine but no significant interaction between age and vaccination time for the antibody response. This is consistent with a recent report studying a retrospective cohort of health care workers immunized with mRNA or Adenovirus SARS-CoV-2 vaccine, which showed no significant interactive effect between age and vaccination time.…”
Section: Discussionsupporting
confidence: 41%
“…[14,15] It was found that children vaccinated attenuated vaccine against poliomyelitis in the morning had better antibody responses compared to those vaccinated in the evening. [9] Recent studies showed that morning vaccination of seasonal influenza [8] or Bacille Calmette-Guerin [16] elicited a stronger trained immunity and adaptive immune response when compared to afternoon vaccination. However, the effect of vaccination time may vary in different vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Other data have implicated humoral immune responses to be highly time-ofday dependent in both the preclinical and the clinical setting, thus linking circadian oscillations in B cells to vaccination efficacy. 74,75 Hematopoietic Stem and Progenitor Cells Hematopoietic stem and progenitor cells (HSPCs) are also known to be subject to circadian regulatory patterns. HSPCs in the bone marrow generate various lineages of blood cells and many of their functions, such as proliferation, differentiation, or trafficking, exhibit timedependent fluctuations that require tight coordination to ensure daily blood cell replenishment in both mice and humans.…”
Section: B Cellsmentioning
confidence: 99%
“…Some theorize that the circadian rhythms in humans should translate, directly or indirectly, into preferable times of day to vaccinate patients 1,2,[19][20][21] . However, clinical studies differ on whether rhythms exist in vaccine responses, including those against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of coronavirus infectious disease-19 (COVID-19) [22][23][24][25][26][27][28][29][30][31] . While important, prior studies had limited sample sizes and focused on markers of immunogenicity like antibody titers rather than clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%